2019
DOI: 10.1101/787325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deletion of Stk11 and Fos in mouse BLA projection neurons alters intrinsic excitability and impairs formation of long-term aversive memory

Abstract: 27Conditioned taste aversion (CTA) is a form of one-trial learning dependent on basolateral 28 amygdala projection neurons (BLApn). Its underlying cellular and molecular mechanisms 29 are poorly understood, however. We used RNAseq from BLApn to identify learning-30 related changes in Stk11, a kinase with well-studied roles in growth, metabolism and 31 development, but not previously implicated in learning. Deletion of Stk11 restricted to 32 BLApn completely blocks memory when occurring prior to training, bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
0
2
1
Order By: Relevance
“…Previous studies have reported robust effects of similar perturbations on palatabilityguided behavior (CTA learning and taste neophobia; Gallo et al, 1992;Lin et al, 2009;Lin and Reilly, 2012;Lavi et al, 2018;Levitan et al, 2020). In our hands, however, the impact of BLA→GCx was less complete, and some GC neurons even gained palatability responses in perturbed trials ( Figure 8B).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Previous studies have reported robust effects of similar perturbations on palatabilityguided behavior (CTA learning and taste neophobia; Gallo et al, 1992;Lin et al, 2009;Lin and Reilly, 2012;Lavi et al, 2018;Levitan et al, 2020). In our hands, however, the impact of BLA→GCx was less complete, and some GC neurons even gained palatability responses in perturbed trials ( Figure 8B).…”
Section: Discussioncontrasting
confidence: 40%
“…Palatability-relatedness in the firing of some single neurons was not utterly eliminated by our input manipulation; in some cases it was even enhanced. This fact is perhaps somewhat surprising given the well-known importance of amygdala for emotion processing (e.g., Quirk et al, 1995;Schoenbaum et al, 1998;LeDoux, 2000;Wang et al, 2005;Wassum and Izquierdo, 2015;Beyeler et al, 2018), and findings suggesting that BLA-GC circuitry is vital for palatability-related behavior (CTA learning and taste neophobia; Gallo et al, 1992;Lin and Reilly, 2012;Levitan et al, 2020). Our recent data suggest a possible explanation, however: as previously discussed, the emergence of Late-epoch palatability coding is revealed, using single-trial analyses involving Hidden Markov Modeling (HMM), to be a sudden transition into a new ensemble state, in which firing-rate changes occur simultaneously in multiple GC neurons (Jones et al, 2007;Miller and Katz, 2010;Sadacca et al, 2016); it is this sudden transition itself that directly drives behavior (Mukherjee et al, 2019).…”
Section: Perturbation Of Bla Input To Gc Attenuates the Ensemble Propmentioning
confidence: 99%
“…By virtue of its extensive network of connectivity, this elongated cortical structure has been shown to integrate sensory, emotional, motivational, and cognitive brain centers through distinct mechanisms. For example, deletions of either Fos or Stk11 in BLA-aIC neurons, alter intrinsic properties at the aIC, and impair CTA acquisition (Levitan et al, 2020). Furthermore, approach behaviors in social decision-making are modulated by subjective and sex-specific affective states that regulate cell-type-specific changes in intrinsic properties at IC terminals receiving hypothalamic input (Rogers-Carter et al, 2018, 2019; Rieger et al, 2022).…”
Section: Introductionmentioning
confidence: 99%